DNA Topoisomerases and Cancer - Pommier, Yves.; Pommier, Yves. (Cancer Drug Discovery and Development, 2012)
DNA topoisomerases are present in all living organisms and are essential to maintaining the helical structure of DNA. They are highly relevant for cancer because a number of anti-cancer drugs selectively target two of the human enzymes, DNA topoisomerases I and II. Those drugs convert topoisomerases into cellular poisons by trapping the enzymes as they cleave DNA. The book starts out with a detailed outline of the phyllogeny of the different topoisomerases, continues with recent studies on the crystal structures of the human topoisomerases, and their biochemistry. The following section reviews the chemical biology of the topoisomerase inhibitors used in cancer chemotherapy and the implication of topoisomerases in generating recombinations and DNA damage. The third section summarizes the current use of the various topoisomerase inhibitors in cancer chemotherapy. And finally, the last section includes several chapters describing the DNA repair pathways for topoisomerase-induced DNA damage. This book is intended for students and faculty but also for health care professionals who wish to have a self-contained and up-to-date information on topoisomerases. Chapters have been written by leaders and world reknowned experts in the topoisomerase field.